2019
DOI: 10.1097/mpa.0000000000001386
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation Promotes Progression of Pancreatic Cancer Through WNT/β-Catenin Pathway-Dependent Manner

Abstract: Objective Identify the molecular mechanism of inflammatory stimuli induced pancreatic cancer progression. Methods RNA-seq, microarray assay and bioinformatics analyses were used to identify differentially expressed genes. Immunohistochemical staining was performed to evaluate CD68, CD163, β-catenin, CD103, CCL3 markers. Quantitative real-time polymerase chain reaction (qRT-PCR), luciferase reporter assay, apoptosis assay, wound healing assay and immunof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Both TGF‐β and WNT signalling were previously reported to be implicated in pancreatic carcinogenesis by promoting the EMT process 46,47 . Ren et al reported that TGF‐β could promote the migration of PC cells by inducing EMT during the activation of WNT signalling pathway 48 . The activation of TGF‐β signalling pathway promotes Treg cells recruitment and TAMs polarization and induces immunosuppression in the TME 49,50 .…”
Section: Discussionmentioning
confidence: 99%
“…Both TGF‐β and WNT signalling were previously reported to be implicated in pancreatic carcinogenesis by promoting the EMT process 46,47 . Ren et al reported that TGF‐β could promote the migration of PC cells by inducing EMT during the activation of WNT signalling pathway 48 . The activation of TGF‐β signalling pathway promotes Treg cells recruitment and TAMs polarization and induces immunosuppression in the TME 49,50 .…”
Section: Discussionmentioning
confidence: 99%
“…CCL3 may be expressed in a cancer cell [ 127 ]. The immune response reduces the expression of CCL3 in cancer cells via the activation of β-catenin [ 129 ]. Both CCL3 and CCL4 are also expressed in chronic myeloid leukemia and multiple myeloma [ 130 , 131 , 132 , 133 ].…”
Section: Ccr5 Ligandsmentioning
confidence: 99%
“…Increased expression of CCL19 and CCL21 in a tumor results in anti-cancer TIL infiltration and an improved prognosis for many tumor patients [ 195 , 196 , 197 , 198 ]. Cancer immune evasion mechanisms reduce the expression of these chemokines in a cancer cell [ 129 ]. Nevertheless, if the tumor microenvironment has favorable conditions for tumor development, then CCL19 and CCL21 may participate in T reg recruitment to the tumor niche [ 226 , 227 ].…”
Section: Ccr7 Ccl19 and Ccl21mentioning
confidence: 99%
“…Phase contrast images were taken at beginning and after 24 hours and 48 hours. The cell migration effects were measured by the closure area of scratch [17]. Invasion assays were performed on an 8μm pore size transwell (BD Falcon cell culture insert, BD Bioscience) with modifications.…”
Section: Wound Closure Assay and Invasion Assaymentioning
confidence: 99%